2021
DOI: 10.1093/rheumatology/keab580
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals key genes modulated by ALK5 inhibition in a bleomycin model of systemic sclerosis

Abstract: Objective Systemic sclerosis (SSc) is a rheumatic autoimmune disease affecting roughly 20 000 people worldwide and characterized by excessive collagen accumulation in the skin and internal organs. Despite the high morbidity and mortality associated with SSc, there are no approved disease-modifying agents. Our objective in this study was to explore transcriptomic and model-based drug discovery approaches for systemic sclerosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For instance, preclinical animal models reproducing tissue alterations of TCs/CD34 + stromal cells, much like those found in human diseases, may clearly represent an invaluable tool for elucidating the effective contribution of these cells to disease pathogenesis and/or pathophysiology, which could often only be supposed [25]. In this context, to our knowledge, this is the first study to investigate TCs/CD34 + stromal cells in the mouse model of bleomycin-induced dermal fibrosis, which is widely used in SSc research [37,38,56]. Indeed, we have previously shown that clinically involved skin of patients with SSc displays a progressive impairment in the dermal network of TCs/CD34 + stromal cells, starting from the early cutaneous disease stage up to almost their complete loss in the advanced stage [31,32].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…For instance, preclinical animal models reproducing tissue alterations of TCs/CD34 + stromal cells, much like those found in human diseases, may clearly represent an invaluable tool for elucidating the effective contribution of these cells to disease pathogenesis and/or pathophysiology, which could often only be supposed [25]. In this context, to our knowledge, this is the first study to investigate TCs/CD34 + stromal cells in the mouse model of bleomycin-induced dermal fibrosis, which is widely used in SSc research [37,38,56]. Indeed, we have previously shown that clinically involved skin of patients with SSc displays a progressive impairment in the dermal network of TCs/CD34 + stromal cells, starting from the early cutaneous disease stage up to almost their complete loss in the advanced stage [31,32].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, further in-depth investigations utilizing this mouse model will hopefully help identifying the pathogenetic mechanisms underlying the damage of TCs, which could even prove useful as novel therapeutic targets to slow down or halt the progression of skin fibrosis. Finally, since the subcutaneous bleomycin mouse model is widely used in the development of novel therapies for SSc [37,56], we believe that verifying if the efficacy of the tested therapeutic approaches associates with a regeneration of the dermal networks of TCs/CD34 + stromal cells might provide new valuable insights into this still enigmatic cellular entity of the skin microenvironment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…WGCNA can be used to find clusters of highly correlated genes, which allows for the identification of key modules [ 24 ]. In this study, WGCNA was conducted to identify gene modules whose expression pattern was found in the in vivo pulmonary toxicity induced by different substances such as polycyclic aromatic hydrocarbons, cigarette smoke, diesel exhaust, ozone, particulate matter, bleomycin, radiation, and nanomaterials, among others ( Table S2 ) [ 10 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Once modules were identified from those publicly available transcriptomic datasets, the biological functions of each module were determined, and GSEA was conducted to ...…”
Section: Methodsmentioning
confidence: 99%